Pedagogical Tools in Our Briefcases: Teaching the Business and Professional Communication Course - Suzy Prentiss (Journal of Communication Pedagogy, 2019)
As a practical and applied course, Business and Professional Communication is an excellent opportunity to blend theory and practice, prepare students with the knowledge and skills they will need in the “real world,” and continually innovate and experiment to meet the ever-changing communication needs of the workplace. Whether filled with students majoring in communication, business or another discipline, as a General Education or sequenced class, the Business and Professional Communication course is a worthwhile and value-added course that is both challenging and rewarding to teach.